Utility and Safety of Perampanel in Pediatric FIRES and Other Drug-Resistant Epilepsies - Guo Yong Lim BSc(Pharm.)(Hons.) (SAGE Publishing, 2021)
Perampanel is a novel antiepileptic drug, which antagonises AMPA (alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) glutamate receptor. We describe perampanel as an adjunctive treatment for FIRES (febrile infection-related epilepsy syndrome) and other drug-resistant epilepsies. A single-centre, observational, retrospective study involving 20 pediatric patients was conducted. Perampanel was started for three patients with FIRES, achieving seizure cessation in two patients within a day and on days 19 and 32 of illness. Doses used ranged from 4 to 12 mg/day, without any adverse effects reported or discontinuation of therapy. Responder-rate for other drug-resistant epilepsies is 25%. Median time to achieve ≥50% seizure reduction was 80 days (range: 26-326 days). Adverse effect reported in 47% of the patients includes central nervous system-related, and thrombocytopenia. Eight patients discontinued perampanel, because of ineffectiveness or adverse effects. The median time on perampanel before discontinuation was 179 days (range: 94-345 days). Perampanel may be of benefit in pediatrics FIRES and is of utility in other drug-resistant epilepsies.